A macroeconomic estimation of wine production in Greece - Vasileios A. Vlachos (Wine Economics and Policy, 2017)
Unlike other south European Union countries with tradition in wine production, Greece has not yet exploited the industry's export potential. However, there are expectations that under certain policy orientations, a competitive industry with internationally recognized labels could emerge. This paper explores the drivers of wine production in Greece from a macro perspective and assesses their impact vis-à-vis international trade in order to contribute to these orientations for the development of a competitive industry that will assist Greece in the search for an exit from economic depression. The findings indicate that international trade impacts more on wine production in Greece than domestic consumption of Greek wine and that productivity boosts wine production at the same time as personnel costs are a significant impediment. Policy orientations based on the findings are discussed.
Keywords: 330; Greece; International trade; Panel data analysis; Wine production